Complementary and Alternative Medicine: Professions or Modalities? Policy Implications for Coverage, Licensure, Scope of Practice, Institutional Privileges, and Research - Herman, Patricia M. (RAND Corporation, 2015)
Using development of a background paper on the policy issues associated with the scope of practice and utilization of complementary and alternative medicine (CAM) in the health care system, input from a panel of CAM experts, and input from a panel of health care policy decisionmakers, this report explores the policy challenges associated with coverage, licensure, scope of practice, institutional privileges, and research among the CAM professions.